1983
DOI: 10.1159/000101244
|View full text |Cite
|
Sign up to set email alerts
|

Diencephalic Seizures

Abstract: Intractable complex partial and diencephalic seizures in 1 patient are being treated effectively by intermittent daily electrical stimulation in the right thalamus in conjunction with phenytoin, 200 mg/day, Electrical stimulation in the right thalamus was found to suppress spike and sharp wave discharge activity temporarily in the right thalamus and in the left parietal and right scalp leads. It was postulated that beneficial effects from electrical stimulation were due to electrically ‘jamming a low-threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Thalamic areas are also able to reduce epileptiform activity if they were stimulated electrically. In humans, electrical stimulation of the centromedial, anterior or reticular nuclei reduced different types of epilepsy 31,32 . In summary, our results suggest that these differences may be particularly important for understanding triggering and spreading mechanisms underlying epileptic activity during status epilepticus and recurrent seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Thalamic areas are also able to reduce epileptiform activity if they were stimulated electrically. In humans, electrical stimulation of the centromedial, anterior or reticular nuclei reduced different types of epilepsy 31,32 . In summary, our results suggest that these differences may be particularly important for understanding triggering and spreading mechanisms underlying epileptic activity during status epilepticus and recurrent seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Salvos of yawning and irrepressible hiccupping accompany this spectacular and very unpleasant profile. The cases described reveal the presence of thalamic tumors [83][84][85][86][87]. D'Mello et al [88] also reported salvos of yawns as an iatrogenic effect of vibratory massage or of the withdrawal of neuroleptics, persisting several months after convulsions are provoked.…”
Section: Excessive Yawningmentioning
confidence: 93%